Molecular geometry from molecular tensegrity: a case study of gas-phase MX2 compounds - Ganguly, Parthasarathy (Current Science, 2006)
We define a tensegrity factor, t(00)(+/-), for X-M-X linkages of gas-phase MXn compounds (X is an atom of an insulating element) that is a measure of the matching of `ideal' 1,2-(single-bonded) M-X distance, d(MX)(00), to the `ideal' (non-bonded) 1,3-X–-X distances, d(MX)(00). The actually observed 1,3-distance, d(XX) is given (within 1% error) by 2CR(X)/F-S, where F-S (= 2-1.41(00)(+/-)) is shown to be an ab initio quantity with no adjustable parameter, no dependence on actual M-X distance or bond order and with 2CR(X) depending only on whether M is an atom of an insulating element (2CR(X) =d(XX)(00)) or whether M is metallic (2CR(X) = 1.1d(XX)(00)). This is illustrated for gas-phase MX2 compounds.
Keywords: gas-phase; molecular geometry; MX2 compounds; tensegrity